Adolescentes em situação de acolhimento institucional prolongado : análise do processo de desligamento - Benetti, Daniella Simões (Universidade Federal de São Carlos, 2012)
The host institution is one of the lines of political action to guarantee the rights of children and adolescents, whose character is provisional and exceptional form of transition to reintegration and family or for integration in a foster family. Usually occurs when families are considered unable to provide child care, or when they have behaviors that put at risk the full development of children. Both the removal of the child or adolescent from family and his dismissal of the institution are made by the Government, however, there is a lack of effective public policies and scientific research data that cover the issue of institutional shutdown, more specifically. The present study aimed to: a) describe the process of institutional shutdown according to the opinion of adolescents who lived in a situation of institutional care for an extended period and the leaders; b) describe the operation of a host institution. This was a qualitative, exploratory. The study included two leaders of the two institutions reception and six individuals who remained in a state of Reception beyond the time allowed by law, and who completed two years of majority, including motive, which led to the shutdown. The instruments used for data collection were: Interview Script 1) The characteristics of the host institution and Interview Script 2) Shutdown Institutional, both were applied with the leaders of institutions and even Home, Interview Script 3) The Consequences Off the Institutional conducted with former accepted. The questions of the interview scripts were submitted before the application, the judges pointed suggestions to better understand the context. The application of the interviews took place at different times and places previously chosen by the participants. By means of the instruments were performed quantitative analyzes, obtained from the defined categories, with the main parameter to content analysis. The results indicated that in some respects the institutions surveyed described themselves differently, therefore, had different types of conduct with regard to the implementation of some of its functions, humanization of the shutdown process, preparation gradual for that time, maintenance of family ties, family support for restructuring, encouraging interaction with other families, participation in the services offered by the local community. Other aspects described by the Institutional leaders have been characterized equally and refer to similar residential maintenance of emotional bonds between siblings, attendance at small groups, among others. Most adolescents showed that the shutdown was a moment Institutional permeated by feelings of sadness, fear, insecurity, memories, and the individual is ready or not to experience this moment and its consequences were related to the difficulty in getting a job, live alone, keep themselves financially. It is concluded that there is need for specific policies that cover the issue of Institutional shutdown, to support the teen financially, emotionally, socially, before, during and after this procedure. Still, training for all social actors involved in institutional care situation for better care and understanding of the context.
Keywords: Educação especial; Estatuto da criança e do adolescente; Fatores de risco e proteção; Acolhimento Institucional; Desligamento Institucional; Institutional Shelter; ACE Risk factors; Institutional shutdown; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL